Dekonstruksi Tren Halal Gen-Z : Praktik Kepatuhan Semu dan Peran Auditor Syariah - Moch. Imam Maulana; Ghiska Meylanie; Lailatul Lutfi; Ferdian Azka; Ika Nurfitriani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The halal trend among Generation Z reflects not only increasing religious awareness but also the transformation of halal into a social identity, lifestyle, and digital consumption strategy. This shift creates major opportunities for the halal industry, yet it also raises the risk of pseudo-compliance through the use of religious symbols, halal claims, influencer promotion, and sharia labels without substantive business practices. This article aims to examine pseudo-compliance in the phenomena of halal washing, influencer-based halal cosmetics, and sharia paylater services, as well as to explain the role of sharia auditors in assessing the alignment between halal claims and operational practices. This study uses a qualitative method with a library research approach by reviewing national and international open-access articles published from 2020 to 2026. The findings show that sharia compliance cannot be assessed only through certificates, labels, or contract terminology, but must be examined through supply chains, ingredients, production processes, marketing ethics, funding sources, contract structures, fees, penalties, and consumer protection. Sharia auditors need to expand their work from administrative inspection to evidence-based substantive auditing. Thus, sharia auditing can serve as an important instrument for maintaining the integrity of the halal industry and preventing the exploitation of religion as a marketing strategy.